ARSITEKTUR DAN PERMUKIMAN KELOMPOK SOSIAL TERPINGGIRKAN DI KOTA DENPASAR - -, Sulistyawati (Jurnal Natah; Vol. 5, No. 2 Agustus 2007, 2012)
Architectural picture of a dwelling area can indicate its social, economic, and cultural features of the community concerned. Indonesia, as one of developing countries, for example, has many dwelling areas for marginalized social groups one of them is Denpasar that often creates architecturally disordered city. The purposes of this paper are to know and understand: (1) the causes of disorder of marginalized dwelling; (2) the negative impacts of the disorder; (3) the solutions for architectural ordering of that dwelling; and (4) the obstacles in implementation of ordering program and its alternative solutions. The findings of this study indicate that the causes of layout and environment disordering of marginalized group in Denpasar are: that this marginalized group is out of planning and facilities development of the city; most of these poor groups earn their livings in informal sector, adding with various small family businesses in very narrow house yard that make supporting facilities crowded and mixed with industrial disposal they create; they tend to choose to live in the cheapest areas and close to the center of the city, no matter how slump it is. Other cause is culture of poverty. Its negative impacts are: hampering of the beauty of the city and waste of resources; sources of various epidemic sicknesses; sources of psychological or mental sicknesses such as hate of staying at home and social emotional sensitive. The ordering solutions need the roles of all concerned, particularly related institutions, non government organizations those concern with the problems of slump areas, either from technique-technological or socio-cultural points of views, with active participation of the society of that slump area. The impeding factors to the implementation of the programs are: the obstacle from the policy makers, solved through mental improvement and understanding the needs of the city poor. The obstacles from the target society and its alternatives to be solved include: land right, the determination to stay, poverty, personal characteristic and behavior of the social group.
Keywords: dwelling architecture of the city poor.